PENGENDALIAN KUALITAS PANEL KOMPOSIT AMPAS KOPI MENGGUNAKAN METODE TAGUCHI - Haryanto, Rizal; Triono, Agus; Asrofi, M; Nurdiansyah, Haidzar; Trifiananto, M (Jurusan Teknik Mesin, 2024)
The use of alternative materials such as composites has been widely used in small scale, medium scale and large scale production. Composites can be interpreted as a new type of engineering material consisting of a combination of two or more different types of material. Composite material will have more superior properties than its constituent material. In this study focused on improving the quality of coffee waste composite panels by increasing tensile strength and reducing the failure in panel manufacturing process. Using three parameter variations, namely washing temperature, water content and curing temperature with three levels for each parameter. This combination is replicated 4 times and confirmation experiments are carried out and processed using the taguchi method with L9 orthogonal array with the help of Minitab software. This research was conducted in the Applied Lab, Department of Mechanical Engineering, Faculty of Engineering, University of Jember to obtain data on results and data processing. The results of the study are based on the value of tensile strength. Analysis of the Taguchi method is done using Minitab software. The test results show that the water content has the highest effect on the response parameters of 40.80% at level 1 with a moisture content of 5%, and in the second parameter, the curing temperature is 27.58% at level 3 of 800C, and at the washing temperature at 24.78% at level 3 of 900C.